METHODS OF PROGRAMMING TEACHING MACHINES FOR SPEECH. - Tolch, Charles John (Speech Teacher)
Focuses on three methods of programming teaching machines and illustrates how speech can be programmed for machine instruction. Importance of automated teaching aids in the enhancement and improvement of teaching-learning methods; Difference between audio-visual aids and teaching machines; Advantages of teaching machines.